Quorum sensing signal autoinducer-2 promotes hydrogen peroxide degradation in water by Gram-positive bacteria - Han, Shuo (2024)
Hydrogen peroxide is widely used to remedy bacterial and parasitic infections, but its excessive use will cause severe damage to aquatic animals. Moreover, there is no safe, efficient and low-cost method to degrade residual hydrogen peroxide in water. Here we developed a hydrogen peroxide removal mechanism by which autoinducer-2 (AI-2), a quorum sensing signal molecule that can promote the hydrogen peroxide degradation by Gram-positive bacteria. Here, we investigated the promotion effect of AI-2 on hydrogen peroxide degradation by Deinococcus sp. Y35 and the response of the antioxidant system. We further sought to understand the key mechanism underlying the promotion effect of AI-2 on hydrogen peroxide degradation is that, AI-2 contributed to the resistance of strain Y35 to oxidative stress induced by hydrogen peroxide, and altered membrane permeability of strain Y35 that allowed more hydrogen peroxide to enter bacterial cells and be degraded. Additionally, AI-2 can also encourage multiple Gram-positive bacteria to degrade hydrogen peroxide. Accordingly, our study serves as a reference for the regulation mechanism of the signal molecule AI-2 and provides the development of new strategies for hydrogen peroxide degradation.